Intersections: audiovisual translation at the crossroads of disciplines. (4th March 2019) - Zanotti, Serenella; Ranzato, Irene
ABSTRACT: This brief article serves as an introduction to the contributions collected in the special issue devoted to interdisciplinarity in audiovisual translation. Using the notion of intersection to reflect on the inherent multidisciplinarity of AVT studies, it offers an overview of recent studies that explore the fruitful methodological intersections and cross-contamination between AVT and other disciplines, stressing 'the independence of AVT as an autonomous discipline and its dependence on other related disciplines' (Romero Fresco 2006). It is argued that multidisciplinary approaches can show the full range of possibilities of AVT research.